A Comprehensive Study on Job Insecurity and Its Impact on Employee Turnover Intention: Mediating Role of Job Satisfaction and Moderating Effects of Organizational and Ethical Factors (Study on Employees of Telecommunication Company) - Diana Gusti Ambarwati; Salamah Wahyuni (Dinasti International Journal of Education Management And Social Science, 2025)
This research aims to analyze the effect of job insecurity on the turnover intention of employees at PT. Telekomunikasi Jakarta. The study also examines the moderating roles of organizational support and ethical leadership, as well as the mediating role of job satisfaction. Through a survey of 240 employees in three IT departments and PLS-SEM analysis, the findings reveal that job insecurity significantly increases employees' desire to leave the company. Organizational support and ethical leadership are shown to strengthen the positive relationship between job insecurity and turnover intention. Conversely, job insecurity significantly decreases job satisfaction, which subsequently reduces turnover intention. Additionally, job satisfaction acts as a significant mediator in the pathway from job insecurity to turnover intention.